Water Spraying Prior to Transportation Reduces Transportation Stress and Maintain the Meat Quality of Broiler Chickens - Tamzil, Mohammad Hasil; Indarsih, Budi; Jaya, I. Nyoman Sukatha (Pakistan Journal of Nutrition, 2018)
Background and Objective: Transportation of broiler chickens triggers the stress responses and reduces the quality of meat. The aim of this study was to evaluate the effects of water spraying of broiler chickens prior to transportation on the hematological status and the quality of broiler meat. Methodology: The study was designed with a one-way completely randomized design using 45 female broilers aged 30 days. The broilers were divided into 3 treatment groups and each group consisted of 15 chickens. Treatment I (control) consisted of broilers chickens without water spraying and transportation. Treatment II consisted of broilers chickens without water spraying prior to transportation. Treatment III consisted of broilers chickens that were water sprayed prior to transportation. Experimental broilers chickens in Treatments II and III were transported using an open vehicle from 09.00 am-12.00 pm. Results: Transportation of experimental broilers chickens increased rectal temperature, erythrocyte level, leukocyte level, heterophile percentage and H/L ratio and decreased lymphocyte percentage, decreased meat pH, water holding capacity, cooking loss and meat tenderness (p<0.01). The water spraying of the broilers chickens shortly prior to transportation resulted in the same hematological status and meat quality as control broilers without water spraying and transportation (p>0.05). Conclusion: Transportation causes the experimental broilers suffer stress and water spraying of the broilers shortly prior to transportation minimizes the stress effect.